ANALISIS YURIDIS KEABSAHAN KONTRAK KERJA ONLINE ANTARA PELAKU USAHA DAN SELEBGRAM - NIM. A1011211112, MUHAMMAD BAYU (Jurnal Fatwa Hukum, 2025)
Abstract The advancement of the digital era has encouraged businesses to utilize social media, including collaborating with Instagram celebrities, to promote products or services. These collaborations generally utilize online work agreements, which differ from conventional agreements, such as the use of digital platforms for document creation and signing. However, questions arise regarding the legal validity of these agreements, particularly regarding copyright protection, content liability, and transparency in the relationship between entrepreneurs and Instagram celebrities. This study analyzes the validity of online work contracts between businesses and Instagram celebrities in Pontianak based on civil law provisions, the Electronic Information and Transactions (ITE) Law, and regulations related to electronic transactions. The research focuses on assessing the validity of digital contracts in current business practices and their legal implications, thus providing an in-depth understanding of the legal force of online work agreements in Indonesia. The development of digital business has driven the rise of online work contracts between businesses and Instagram celebrities, but their legal validity still requires further study. This study aims to analyze the validity of digital work contracts under Article 1320 of the Civil Code and the Electronic Information and Transactions (ITE) Law and identify legal risks such as issues of proof and copyright protection. The research method employed a normative-juridical and descriptive-qualitative approach, using primary data from interviews with business owners and Instagram celebrities in Pontianak, as well as secondary data in the form of legal regulations and related literature. The results are expected to provide a comprehensive understanding of the legal force of digital contracts in current business practices, while also uncovering challenges in their implementation, such as uncertainty in proving and protecting the rights of the parties. This study also analyzes the valid requirements for digital employment agreements according to Article 1320 of the Civil Code, the Manpower Law, and the Electronic Information and Transactions (ITE) Law, including the parties' agreement, legal capacity, clarity of the object of the work, and compliance with legal provisions. The legal consequences of failing to meet these requirements are also discussed, such as contract cancellation, administrative sanctions, or criminal prosecution. The results indicate that online employment contracts are legally valid as long as they meet formal and material requirements and use a verified electronic signature. The implications of this research provide guidance for business owners and Instagram celebrities in drafting legally secure digital contracts, while also strengthening legal certainty in electronic transactions in Indonesia. Keywords: online employment contracts, Instagram celebrities, legal validity, Electronic Information and Transactions (ITE) Law, digital business, electronic agreements Abstrak Perkembangan era digital telah mendorong pelaku usaha untuk memanfaatkan media sosial, termasuk berkolaborasi dengan selebgram, guna mempromosikan produk atau jasa. Kerja sama ini umumnya menggunakan perjanjian kerja online yang memiliki karakteristik berbeda dari perjanjian konvensional, seperti penggunaan platform digital dalam pembuatan dan penandatanganan dokumen. Namun, muncul pertanyaan mengenai keabsahan hukum perjanjian tersebut, terutama terkait perlindungan hak cipta, tanggung jawab konten, dan transparansi hubungan antara pengusaha dan selebgram. Penelitian ini menganalisis keabsahan kontrak kerja online antara pelaku usaha dan selebgram di Pontianak berdasarkan ketentuan hukum perdata, UU ITE, serta peraturan terkait transaksi elektronik. Fokus penelitian adalah menilai validitas kontrak digital dalam praktik bisnis saat ini serta implikasi hukumnya, sehingga memberikan pemahaman mendalam mengenai kekuatan hukum perjanjian kerja online di Indonesia. Perkembangan bisnis digital mendorong maraknya kontrak kerja online antara pelaku usaha dan selebgram, namun keabsahan hukumnya masih perlu dikaji lebih mendalam. Penelitian ini bertujuan menganalisis validitas kontrak kerja digital berdasarkan Pasal 1320 KUHPerdata dan UU ITE, serta mengidentifikasi risiko hukum seperti masalah pembuktian dan perlindungan hak cipta. Metode penelitian menggunakan pendekatan normatif yuridis dan kualitatif deskriptif, dengan data primer dari wawancara pelaku usaha dan selebgram di Pontianak, serta data sekunder berupa regulasi hukum dan literatur terkait. Hasil penelitian diharapkan memberikan pemahaman komprehensif mengenai kekuatan hukum kontrak digital dalam praktik bisnis saat ini, sekaligus mengungkap tantangan dalam implementasinya, seperti ketidakpastian pembuktian dan perlindungan hak para pihak. Penelitian ini juga menganalisis syarat sah perjanjian kerja digital menurut Pasal 1320 KUHPerdata, UU Ketenagakerjaan, dan UU ITE, termasuk kesepakatan para pihak, kecakapan hukum, kejelasan objek pekerjaan, dan kesesuaian dengan ketentuan hukum. Dibahas pula akibat hukum jika syarat-syarat tersebut tidak terpenuhi, seperti pembatalan kontrak, sanksi administratif, atau tuntutan pidana. Hasil penelitian menunjukkan bahwa kontrak kerja online memiliki kekuatan hukum yang sah selama memenuhi persyaratan formal dan material, serta menggunakan tanda tangan elektronik yang terverifikasi. Implikasi penelitian ini memberikan panduan bagi pelaku usaha dan selebgram dalam menyusun kontrak digital yang aman secara hukum, sekaligus memperkuat kepastian hukum dalam transaksi elektronik di Indonesia. Kata kunci: kontrak kerja online, selebgram, keabsahan hukum, UU ITE, bisnis digital, perjanjian elektronik